Dada and surrealist art; with 851 illustrations including 60 handmounted colour plates. - Rubin, W.S. (London : Thames and Hudson, 1969)
Abd-el-Krim ; Abel, Lionel ; Albert-Birot, Pierre ; Alexandrian, Sarane ; Allégret, Marc ; Alloway, Lawrence ; Alquié, Ferdinand ; Appolinaire, Guillaume ; Aragon, Louis ; Arcimboldo, Guiseppe ; Arensberg, Walter ; Arman ; Arnim, Achim von ; Arp, François ; Arp, Hans (Jean) ; Artaud, Antonin ; Artigas, Josep LLorens ; Ashton, Dore ; Auric, Georges ; Baader, Johannes ; Baargeld, Johannes Theodor ; Balakian, Anna ; Baldung, Hans ; Ball, Hugo ; Balla, Giacomo ; Barr, Alfred H. Jr. ; Barrault, Jean-Louis ; Barrès, Maurice ; Barzun, Henri Martin ; Basch, Victor ; Bataille, Georges ; Baudelaire, Charles ; Baur, John ; Bazaine, Jean ; Baziotes, William ; Bellmer, Hans ; Bellows, George ; Berman, Eugene ; Bernier, Jean ; Bertrand, Aloysius ; Blake, William ; Bleuler, Egon ; Bloch, Suzi ; Boccioni, Umberto ; Böcklin, Arnold ; Bonnard, Pierre ; Bouguereau, William Adolphe ; Bourdelle, Emile-Antoine ; Bracelli, Giovanni Batista ; Brancusi, Constantin ; Brandi, Cesare ; Braque, Georges ; Brauner, Victor ; Bresdin, Rodolphe ; Breton, André ; Brion, Marcel ; Buffet, Bernard ; Buffet-Picabia, Gabrielle ; Bunuel, Luis ; Caillois, Roger ; Calas, Nicolas ; Calder, Alexander ; Camfield, William ; Campendonck, Heinrich ; Camus, Albert ; Carrà, Carlo ; Carrington, Leonora ; Carrouges, Michel ; De Casseres, Benjamin ; Cassou, Jean ; Cendrars, Blaise ; Cézanne, Paul ; Chagall, Marc ; Chaplin, Charlie ; Char, René ; Cheval, Ferdinand ; De Chirico, Giorgio ; Christo ; Citroen, Paul ; Clair, René ; Clavaud, Armand ; Cocteau, Jean ; Cohen, George ; Constable, John ; Copley, William ; Cornell, Joseph ; Cortesi, Alexandra ; Cravan, Arthur ; Crevel, René ; D'Aurevilly, Barbey ; Dali, Gala ; Dali, Salvador ; Debussy, Claude ; Degas, Edgar ; Delacroix, Eugène ; Delaunay, Robert ; etc.
boek